Evaluation factors for determining the quality of life of physically independent elderly - Costa, Viviane de Souza Pinho; Molari, Mário; Santos, João Paulo Manfré dos; Freitas, Eliane Regina Sernache de; Jr, Rubens Alexandre da Silva; Fernandes, Karen Barros Parron (Manual Therapy, Posturology & Rehabilitation Journal, 2015)
Introduction: Brazil has experienced an epidemiological transition process, characterized by an aging population, with a rise in chronic diseases and reduction in infectious diseases. In this context, aging brings about the presence of multimorbidities and the use of multiple drugs associated with a worse quality of life of those people. Objectives: To analyze the determinants of quality of life in physically independent elderly. Method: Cross-sectional study of 498 elderly physically independent, divided into three groups according to the presence of comorbidities: I) Control group: no comorbidities; II) Group comorbidities: <3 comorbidities; and III) multimorbidities Group: ≥ 3 comorbidities and were also stratified on the use of medications in: I) Control group: non-medicated; II) medicated Group: <3 drugs; and III) polymedicated Group: ≥ 3 drugs. Structured questionnaires were applied to survey data on socio-demographic characteristics, history of comorbidities and medication use, as well as the SF-36 questionnaire as a quality of life assessment method. Results: Statistically significant differences were found in the quality of life regarding gender, educational level, economic status and multimorbidities. The results show that in elderly populations there is inequality in non-white races and among women in matters regarding access to health services. These groups show bigger probability to have more serious chronic conditions and a bad perception of health and quality of life. It is also very clear that in third world countries, a lot of elderly live in poverty having difficulties in the area of health, a major challenge to the implementation of public policies for the care of those people. Lastly, the results make it evident that the aging process has a direct relationship to the amount of installed diseases and increased use of medications. Conclusion: As much as the results showed that the decline of quality of life in physically independent elderly is related to the presence of multimorbidities and high medication intake, researchers state that people can age with a good quality of life if they opt for a successful aging process where significant activities gain space along with daily actions.